Regulate to facilitate: A scoping review of prefrontal asymmetry in sport and exercise. (May 2022) - Haehl, Wiebke; Mirifar, Arash; Beckmann, Jürgen
Abstract: Background: Prefrontal asymmetry (PFA) describes the relative activity of the right PFC compared to the left PFC. It has been shown that PFA is associated with affective and motivational variables in several contexts, including sport and exercise. Considering the significant roles of affect and motivation in different performance settings, PFA might also be an important indicator of athletic performance. However, the relevance of PFA in the sport and exercise setting has not yet been addressed in its entirety. Instead, previous systematic reviews have solely focused on affective variables. Mapping out the complex interactions between PFA and affective, motivational as well as performance variables could help to understand what determines successful athletic performance as well as the positive psychological effects associated with exercise. Approach: Scientific databases were searched for quantitative studies in English language published in international peer-reviewed journals. All 27 selected studies assessed physical activity and measured PFA in the brain locations F4-F3 and/or F8-F7 using electroencephalography. Findings: The majority of the studies used a non-athlete sample (78%) and exercise types were diverse. While all studies focused on affective or motivational processes, 19% also reported associations with performance. Even though findings are inconsistent, they support the assumption that PFA plays a role in self-regulation. Conclusion: There is evidence for an involvement of PFA in affective, motivational and performance processes in the sport and exercise setting that can be interpreted as regulatory mechanisms. Future research on the underlying mechanisms is warranted, in particular, associations with motivational processes and performance need to be investigated more explicitly. Highlights: The scope of the literature on prefrontal asymmetry (PFA) goes beyond affective processes. Left-hemispheric PFA was associated with increased motivation. Adaptive changes in PFA seem to be related to successful athletic performance. Evidence points toward an involvement of PFA in self-regulatory mechanisms.